15.8k views
1 vote
F m(x) = x2 + 3 and n(x) = 5x + 9, which expression is equivalent to (mn)(x)?

A.5x3 + 9x2 + 15x + 27
B. 25x2 + 90x + 84
C. x2 + 5x + 12
D. 5x2 + 24

User Ztsv
by
5.4k points

2 Answers

3 votes
To find mn(x), we multiply the given functions m(x) and n(x), to get (x^2 + 3)(5x + 9) = 5x^3 + 9x^2 + 15x + 27. No further simplification is necessary.

This is choice A. Note that by inspection, it can be seen that m(x) * n(x) should result in a cubic expression, and only A has a cubic term 5x^3, while the rest only have up to quadratic (x^2) terms.
User Garik
by
5.8k points
2 votes
m(x) = x² + 3 and n(x) = 5x + 9
By multiplying the two functions∴ (mn) (x) = (x² + 3)(5x+9)
= x² (5x+9) + 3(5x+9)
= 5x³ + 9x² + 15x +27

The correct answer is option A //
A.5x3 + 9x2 + 15x + 27



User HRJ
by
5.1k points